2006
DOI: 10.1152/ajpheart.00377.2006
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-mediated activation and mitochondrial translocation of calpain regulates MMP-9 in MVEC

Abstract: . Homocysteine-mediated activation and mitochondrial translocation of calpain regulates MMP-9 in MVEC. Am J Physiol Heart Circ Physiol 291: H2825-H2835, 2006. First published July 28, 2006 doi:10.1152/ajpheart.00377.2006 is associated with atherosclerosis, stroke, and dementia. Hcy causes extracellular matrix remodeling by the activation of matrix metalloproteinase-9 (MMP-9), in part, by inducing redox signaling and modulating the intracellular calcium dynamics. Calpains are the calcium-dependent cysteine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 36 publications
1
76
0
Order By: Relevance
“…3,4) It was also proven that Hcy can upregulate the activity of MMPs 2 and 9. 5,6) Another experimental study showed that Hcy could cause electro-physiological disturbances of potassium currents in human atrial myocytes. 14) On the other hand, recent data also support the involvement of Hcy in oxidative stress and reduced nitric oxide bioavailability in animal heart tis- sue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4) It was also proven that Hcy can upregulate the activity of MMPs 2 and 9. 5,6) Another experimental study showed that Hcy could cause electro-physiological disturbances of potassium currents in human atrial myocytes. 14) On the other hand, recent data also support the involvement of Hcy in oxidative stress and reduced nitric oxide bioavailability in animal heart tis- sue.…”
Section: Discussionmentioning
confidence: 99%
“…3,4) It has been shown in animal studies that metalloproteinases in endocardial cells could be activated by homocysteine (Hcy). 5,6) Elevated levels of Hcy are associated with an increased risk of coronary artery disease and cerebrovascular disease. [7][8][9] One study showed that elevated levels of Hcy are associated with the presence of nonvalvular AF.…”
mentioning
confidence: 99%
“…Fg-induced phosphorylation of ERK was studied using a method described previously [36]. Confluent MVECs were serum starved for 16 h and incubated with one of the following: Fg (2 or 4 mg/ml), Fg (4 mg/ml) with antibody against ICAM-1 (50 μM), Fg (4 mg/ml) with antibodies against α 5 and β 1 , or β 3 integrins (50 μM each), or Fg (4 mg/ml) with MEK inhibitors PD98059 or U0126 (50 μM each) at 37°C for 30 min.…”
Section: Fg-induced Erk Phosphorylation Assaymentioning
confidence: 99%
“…Mitochondrial dysfunction was considered as one of the mechanisms of myocardial damage following NMDAR hyperactivation (45)(46)(47)(48)(49). Ca 2+ overload in cardiomyocytes was suggested to be involved in pathological response to the stimulation with high doses agonists of the NMDAR (47).…”
Section: Characterization Of Cardiac Nmdarsmentioning
confidence: 99%